1998
DOI: 10.1177/074193259801900103
|View full text |Cite
|
Sign up to set email alerts
|

Using Concept Maps to Measure Conceptual Change in Preservice Teachers Enrolled in a Multicultural Education/ Special Education Course

Abstract: Researchers in fields outside of special education have found that concept maps reveal changes in student cognitions as a result of course enrollments and clinical experiences. Hence, we used concept maps to trace conceptual change in preservice teachers enrolled in an introductory multicultural/special education course at Michigan State University (MSU). We analyzed pre- and post-concept maps, explanatory paragraphs, and comparative essays of 30 randomly selected undergraduate students enrolled in the course.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…This reduction of concepts and links is contrary to the findings of Trent et al (1998) in their study of pro-service student teachers in an introductory education course. They identified significantly more concepts from pro-to post-maps about beliefs of effective teaching with an increase in the number of relations to central concepts.…”
Section: Developing Integrated Conceptual Structures In the Ping Collcontrasting
confidence: 82%
See 1 more Smart Citation
“…This reduction of concepts and links is contrary to the findings of Trent et al (1998) in their study of pro-service student teachers in an introductory education course. They identified significantly more concepts from pro-to post-maps about beliefs of effective teaching with an increase in the number of relations to central concepts.…”
Section: Developing Integrated Conceptual Structures In the Ping Collcontrasting
confidence: 82%
“…At the beginning of the course three groups placed the concept "Me and Water" at the centre of their map, two placed "water circulation," one placed "pond" and one "rain." The centre is defined by the focal node with the greatest number of links (Trent, Pernell, Mungai, & Chimedza, 1998). After'teaching two groups changed the central concept to "water quality" and one group had no links at all with no central point.…”
Section: Developing Integrated Conceptual Structures In the Ping Collmentioning
confidence: 99%
“…Results from this mixed methods design revealed similarities and differences between students' pre-and postmaps; in general, students' postcourse paragraphs were consistent with the pre-and postmaps. Also, like Trent et al (1998), they found that teacher candidates developed a "broader definition of diversity after the course, a shift from the general to the specific, and new concepts in the postcourse maps related to instruction and curriculum that were not present in the precourse maps" (p. 338). Although Correa et al found the use of concept maps beneficial, they also recommended the use of multiple tools (e.g., interviews and observations) to trace conceptual change in teachers during their enrollment in their TEPs.…”
Section: Special Education Studiesmentioning
confidence: 96%
“…Concept mapping was developed by researchers in Cornell University for representing conceptual knowledge structures (Novak & Gowin, 1984; Novak & Musonda, 1991). Several qualitative and quantitative studies have shown that with the help of concept maps, meaningful learning can be effectively promoted, such that positive effects can act upon students (Horton et al , 1993; Trent, Pernell, Mungai & Chimedza, 1998). Furthermore, concept maps can also be a visualised cognitive tool supported by computer systems (Anderson‐Inman & Ditson, 1999; Fischer, Bruhn, Grasel & Mandl, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%